Attraction and Accessibility of Investments in Residential Real Estate Depending on the Region - Stoencheva, Yana (Research Papers, 2020)
The present study is dedicated to the complex approach in the analysis of the situation and the trends of key characteristics of the real estate market in Bulgaria by regions. The purpose is to meet the needs of all the players on the real estate market for residential properties in the district cities in Bulgaria, for up-to-date information about the trends and the state of the fluctuations in the return on investment and about the potential possibilities for the active part of the population to participate in the purchase of properties. Tried and tasted various methods have been combined in an appropriate way with the aim of producing completely new and comprehensive analytical results. By utilising complex criteria, we have singled out indicators for the investment attraction and accessibility of the investments in residential properties in district town of the country. The principle of homogeneity is preserved for the totality used, the fluctuation due to inflation are ignored; we have attempted to build on the routine analysis of the price dynamics and the return on investment for the purchase of residential real estate.